Are We Being Served? Emotional Labour in Local Government in Victoria, Australia. Issue 3 (15th October 2017) - Rayner, Julie; Lawton, Alan
Abstract: This paper explores how front‐line street‐level bureaucrats (SLBs) cope with the expectations of citizens, clients, or 'customers' in daily work and how SLBs may be impacted by emotional labour. The study analyses data from 41 interviews with SLBs in local councils in Victoria, Australia. Although exploratory, it builds awareness and understanding of the emotional labour associated with public service. The situations that SLBs engage with on a daily basis are many and varied and take the form of increased expectations and intense encounters. Respondents experienced abuse, threats, violence, but also 'sparkle moments'. Resources that helped SLBs cope are diverse and located both within and outside organisations. Implications are discussed and issues that merit additional investigation are raised concerning how SLBs can be supported to better meet the demands of the public. The research is of value to public managers and SLBs operating in a changing society with increased 'customer' expectations. Abstract : It explores how front‐line street‐level bureaucrats (SLBs) deal with the expectations of customers in daily work and how this may be impacted by emotional labour. The study analyses data from 41 interviews with SLBs in local councils in Victoria, Australia and identifies the resources that enable SLBs to cope.